2015
DOI: 10.1093/schbul/sbv188
|View full text |Cite
|
Sign up to set email alerts
|

Altered Neural Correlate of the Self-Agency Experience in First-Episode Schizophrenia-Spectrum Patients: An fMRI Study

Abstract: During self-agency experience, FES demonstrate deficit in engagement of cortical midline structures along with substantial attenuation of anti-correlated DMN/CEN activity underlying normal self/other-agency discriminative processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 60 publications
1
18
0
Order By: Relevance
“…Backasch et al showed low functional connectivity between the inferior frontal gyrus and some regions (the insula, putamen, and medial orbitofrontal cortex) in schizophrenia by using their own agency task with unintentional movement and delayed visual feedback (20). Spaniel et al demonstrated an impaired default mode and central executive networks dynamic switching in schizophrenia by using their own agency task with incongruent visual feedback (37). Although their task designs were useful for evaluating one neural network, they did not target the learning process in agency adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…Backasch et al showed low functional connectivity between the inferior frontal gyrus and some regions (the insula, putamen, and medial orbitofrontal cortex) in schizophrenia by using their own agency task with unintentional movement and delayed visual feedback (20). Spaniel et al demonstrated an impaired default mode and central executive networks dynamic switching in schizophrenia by using their own agency task with incongruent visual feedback (37). Although their task designs were useful for evaluating one neural network, they did not target the learning process in agency adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, an extensive body of research suggested that inferior parietal cortical, including angular gyrus activation reflected the experiences of agency by processing action signals generated in the frontal cortex (Renes, van Haren, Aarts, & Vink, 2015;Maurer et al, 2016;Voss, Chambon, Wenke, Kuhn, & Haggard, 2017). Other studies implicated the default mode network (Fukushima, Goto, Maeda, Kato, & Umeda, 2013;de Bezenac, Sluming, Gouws, & Corcoran, 2016;Spaniel et al, 2016). A meta-analysis suggested the role of the insula in self-agency across multiple behavioral tasks (Sperduti, Delaveau, Fossati, & Nadel, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…We analyzed a sample of 120 participants with FEP and 114 healthy participants (see Table 1 ). These analyses are a part of the Early Stages of SZ study ( 22 , 23 ). To ensure generalizability, we recruited participants during their first hospitalization in a large general psychiatry hospital (1,200 beds), which serves the Prague and part of Central Bohemia regions—catchment area of over 1.5 million subjects.…”
Section: Methodsmentioning
confidence: 99%